Not all gallantry, gongs and glory: wartime in popular american novels - Adrianna Białecka; Barbara Ewa Struk (Rozprawy Społeczne)
Abstract This article discusses perceptions of World War II in modern American literature. Authors acknowledge novels inspired by their authors’ combat, and discuss visions of war, aims of wartime literature and major literary archetypes.